Igreja e Estado no Brasil oitocentista: um diálogo com La Iglesia católica y la formación del Estado-nación en América Latina en el siglo XIX. El caso colombiano, de Luis Javier Ortiz Mesa - Martins, William de Souza (2022)
The article intends to compare the relationship between State and Churchin Brasil and Colombia during the nineteenth century. In both nations thereare some similarities – as the diffusion of liberal and anticlerical ideas andthe permanence of patronage over the Church –, but we can also identifystrikingly differences. The most important perhaps in degree of radicalismand the political partisanship present in the disputes between the liberaland Ultra Catholic Colombians.